Detours of tourism in the Iguassu: Falls binational tourist destination - Sandi, Simone Maria; Baptista, Maria Luiza Cardinale (Revista Hipótese, 2024)
The article aims to present the different accesses to the Iguaçu Falls, from both the Brazilian and Argentine sides, aiding in the understanding of the singularities of the routes and the ecosystemic nature of the paths and detours. Thus, it contributes to the discussion on the optimal use of the tourist destination with the necessary prior preparation for the success of the tourist experience, considering various variables. This is a partial report of qualitative research on the demand profile and expectations of tourists wishing to visit the region. The methodological strategy is the Cartography of Knowledge (Baptista; Eme, 2023), a proposition derived from investigative trails: 'Entrelaços-Nós da Pesquisa' (keywords); Personal Knowledge of the authors resulting from experiences with the region; Theoretical-Conceptual-Bibliographic Framework, involving authors such as Baptista (2019), Barretto (2004), Marujo (2016), Pezzi and Vianna (2015), Pimentel (2010); Production Plant, involving various procedures in the research process, and the Intuitive Dimension of Research, which is present throughout the journey.
Keywords: Iguaçu Falls; Tourism; Touristic experience